A review of spatio-temporal pattern analysis approaches on crime analysis - Leong, Kelvin (International e-journal of criminal sciences, 2015)
This review aims to summarize spatio-temporal pattern analysis approaches for crime analysis. Spatio-temporal pattern analysis is a process that obtains knowledge from geoand- time-referenced data and creates knowledge for crime analysts. In practice, knowledge needs vary amongst different situations. In order to obtain relevant types of knowledge, different types of spatio-temporal pattern analysis approaches should be used. However, there is a lack of related systematic review which discussed how to obtain related knowledge from different types of spatio-temporal crime pattern. This paper summarizes spatio-temporal patterns into five major categories: (i) spatial pattern,(ii) temporal pattern, (iii) frequent spatio-temporal pattern, (iv) unusual spatio-temporal pattern and (v) spatio-temporal effect due to intervention. In addition, we also discuss what knowledge could be obtained from these patterns, and what corresponding approaches, including various data mining techniques, could be used to find them. The works of this paper could provide a reference for crime analysts to select appropriate spatio-temporal pattern analysis approaches according to their knowledge needs.